Peningkatan Hasil Belajar Pendidikan Agama Islam Siswa Melalui Media Pembelajaran Video di SDN 02 Koto Tinggi - Nelvi Yerni; Sri Hardina; Alhusni Fuad; Roza Elfira; Fadhila Yusri; Adi Warman (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low learning outcomes of Islamic Religious Education of students at UPTD SDN 02 Koto Tinggi. Video media is the most appropriate and accurate learning media in conveying messages and will really help students' understanding. The aim of this research is to: determine the increase in results students learn Islamic Religious Education (PAI) through video learning media at UPTD SDN 02 Koto Tinggi. The data collection techniques used are tests and observations. The results of the research show that video media in PAI subjects is able to increase students' learning motivation, especially class V students at SDN 02 Koto Tinggi. Quantitative evidence can be seen of an increase in the motivation variable test from the first and second meetings. The test results also experienced an increase from pre-action results of 45%, in cycle I (first) it increased to 60%, in cycle II (second) it also increased to 90%. Meanwhile, qualitative evidence can be explained from the number of students who said they were happy the use of video media increases motivation and student concentration on subjects, PAI.